Ammonium application mitigates the effects of elevated carbon dioxide on the carbon/nitrogen balance of Phoebe bournei seedlings. (14th February 2021) - Wang, Xiao; Wei, Xiaoli; Wu, Gaoyin; Chen, Shengqun
Abstract: The study of plant responses to increases in atmospheric carbon dioxide (CO2 ) concentration is crucial to understand and to predict the effect of future global climate change on plant adaptation and evolution. Increasing amount of nitrogen (N) can promote the positive effect of CO2, while how N forms would modify the degree of CO2 effect is rarely studied. The aim of this study was to determine whether the amount and form of nitrogen (N) could mitigate the effects of elevated CO2 (eCO2 ) on enzyme activities related to carbon (C) and N metabolism, the C/N ratio, and growth of Phoebe bournei (Hemsl.) Y.C. Yang. One-year-old P. bournei seedlings were grown in an open-top air chamber under either an ambient CO2 (aCO2 ) (350 ± 70 μmolmol −1 ) or an eCO2 (700 ± 10 μmolmol −1 ) concentration and cultivated in soil treated with either moderate (0.8 g per seedling) or high applications (1.2 g per seedling) of nitrate or ammonium. In seedlings treated with a moderate level of nitrate, the activities of key enzymes involved in C and N metabolism (i.e., Rubisco, Rubisco activase and glutamine synthetase) were lower under eCO2 than under aCO2 . By contrast, key enzyme activities (except GS) in seedlings treated with high nitrate or ammonium were not significantly different between aCO2 and eCO2 or higher under eCO2 than under aCO2 . The C/N ratio of seedlings treated with moderate or high nitrate under eCO2 was significantly changed compared with the seedlings grown under aCO2, whereas the C/N ratio of seedlings treated with ammonium was not significantly different between aCO2 and eCO2 . Therefore, under eCO2, application of ammonium can be beneficial C and N metabolism and mitigate effects on the C/N ratio.